INTERVENING ROLE OF TOURISTS’ ENGAGEMENT IN USER-GENERATED CONTENT ON THEIR PRO-ENVIRONMENTAL BEHAVIOURS: A PERSPECTIVE OF VIRTUAL GOFFMAN’S THEORY - Huayu TANG; Choy Leong YEE; Jo Ann HO; Yanning CHEN (Geo Journal of Tourism and Geosites)
Social media users on platforms like Weibo and XiaoHongshu influence how tourists present themselves online. However, their impact on actual tourist behaviours at destinations remains unclear. This study explores the influence of impression management motivation and online social comparison on tourists’ engagement in pro-environmental user-generated content (UGC) on social media platforms in China. The research investigates how these factors impact tourists’ proenvironmental behavioural intentions (TPBI) using Virtual Goffman's Theory and Social Comparison Theory as the framework. A survey of 716 social media users who had recent travel experiences in China was conducted to examine the psychological mechanisms driving tourists to participate in pro-environmental activities both online and offline. The structural equation model (SEM) results reveal that while impression management motivation did not directly influence pro-environmental UGC engagement, its impact became significant when moderated by the frequency of social media status updates. Online social comparison had a direct positive impact on pro-environmental travel UGC engagement, while social media stalking did not. Proenvironmental travel UGC engagement was found to be a strong predictor of pro-environmental behavioural intention. These findings offer valuable insights into how social media interactions foster eco-conscious behaviours, highlighting the role of impression management and online comparisons in shaping both online and offline pro-environmental actions. The study provides implications for promoting sustainable tourism practices through social media engagement strategies.